Some ecological aspects of the helminthic fauna of the red fox (Vulpes vulpes L.) of the Palaerctic zone : II-vulpine iberian populations - Varela, Manuel Carvalho (2013)
Com base na acentuada discrepância na criação de subespécies da raposa-vermelha (Vulpes vulpes L.) da zona Palcártica, os autores comparam os elementos disponíveis inerentes à helmintofauna da população vulpina da península Ibérica, França e alguns países do Norte de África. Pretendem, assim, complementar as opiniões dos zoologistas e zoogeógrafos, de modo a confirmar uma definição taxonómica mais correcta , de acordo com as propostas formuladas na primeira parte do nosso trabalho (CARVALHO-VARELA et al., 1985).--- Based on the marked discrepancy in the establishement of sub-species of the red fox (Vulpes vulpes L.) of the Palacartic Zone, the authors compare the helmintic fauna of the vulpine population of the Iberian Peninsula, France and some north African countries. Therefore we wish to complement the opinions of zoologists and zoogeographers in order to validate a more correct taxonomic definition, according to the proposals formulated in the first of our paper (CARVALHO-VARELA et al., 1985).